ANALISIS KEMAMPUAN PENGUASAAN MATERI PECAHAN DAN OPERASI HITUNGNYA PADA SISWA KELAS VI SEKOLAH DASAR - Luh Tri Utami; I Made Ari Winangun; Ni Nyoman Lisna Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The study discusses the ability to master fractions and their arithmetic operations in sixth grade students of SDN 1 Sari Mekar. This study aims to describe the ability to master fractions and their arithmetic operations in sixth grade students of SDN 1 Sari Mekar, Buleleng Regency. This study uses a survey method using a population of sixth grade students of SDN 1 Sari Mekar with a sample of 27 students. The results of the study show results with the lowest score being 40, the highest score being 100, an average of 72.59 and a standard deviation of 24.43. The results of the study showed that students in the high score category with a score range of more than or equal to 97.02 were obtained as many as 10 students with a percentage of 37.04%, students in the medium score category with a score range of more than or equal to 48.16 and less than or equal to 97.02 were obtained as many as 16 students with a percentage of 59.26% and students in the low score category with a score range of more than or equal to 48.16 and less than or equal to 97.02 were obtained as many as 1 student with a percentage of 3.7%. Based on these data, the average results of students' mastery abilities on fractions and arithmetic operations in the population are in the medium category.